2018
DOI: 10.1051/matecconf/201819015014
|View full text |Cite
|
Sign up to set email alerts
|

Material flow control in plunge micro rotary swaging

Abstract: In rotary swaging, the material flow is not fully controlled by closure of the forming dies. This is especially noticeable in plunge rotary swaging of rod, where the workpiece is positioned into the forming zone und processed locally. As result, an uncontrolled elongation of the workpiece in axial direction takes place and an axial position shift of the workpiece relative to the dies occurs. This is a special challenge in production of linked micro parts, where single parts are interconnected in order to enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Figure 2.19 shows the final diameters after a reduction of rods from AISI 304 steel with an initial diameter of d 0 = 1.0 mm using a die set with a nominal diameter of d nom = 0.75 mm and a calibration zone of l cal = 20 mm. For low feed rates (v f < 4 mm/s), d 1 is constant over the workpiece length and close to d nom [Mou18a]. At high feed rates, however, the diameter evolves over the workpiece axis z'.…”
Section: High Productivity In Infeed Swagingmentioning
confidence: 76%
See 3 more Smart Citations
“…Figure 2.19 shows the final diameters after a reduction of rods from AISI 304 steel with an initial diameter of d 0 = 1.0 mm using a die set with a nominal diameter of d nom = 0.75 mm and a calibration zone of l cal = 20 mm. For low feed rates (v f < 4 mm/s), d 1 is constant over the workpiece length and close to d nom [Mou18a]. At high feed rates, however, the diameter evolves over the workpiece axis z'.…”
Section: High Productivity In Infeed Swagingmentioning
confidence: 76%
“…In order to control the material flow against the axial feed direction and thus prevent process limitations like bending or even breaking, a spring-loaded clamping device for the workpiece was developed [Mou18a]. The clamping device allows an axial evasion of the workpiece.…”
Section: High Productivity In Infeed Swagingmentioning
confidence: 99%
See 2 more Smart Citations
“…It could be shown that the effect on the part geometry can be more or less significant depending on the machine parameters. As shown in [Mou18], a convenient control of the applied forces or a compensation of the elongation improves the forming results and enables the production of symmetrical parts without defects.…”
Section: Effects Resulting From the Production As Linked Partsmentioning
confidence: 99%